Pengembangan Media Timeline Interaktif Untuk Meningkatkan Kemampuan Berpikir Kronologis Siswa - Laura Tsurayya Nory; Ofianto Ofianto (Jurusan Sejarah FIS UNP, 2020)
This study aims to: 1) Know how the process of developing interactive timeline media for the history learning of high school students in grade XI. 2) Analyzing the feasibility of the media and the effectiveness of learning after using the interactive timeline media for class XI students at SMAN 2 Padang. The method used is research development, by following the steps of developing the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The subject of this research trial consisted of 33 students of SMA Negeri 2 Padang class XI IPS 2. In this study a feasibility test was conducted based on the assessment of 2 material experts and 2 media experts to see the feasibility of the media before the trial. In addition, practicality tests were also conducted by history class XI teachers and 33 students to see the practicality of the interactive timeline media. The results showed that the feasibility of the media based on the assessment of the material experts stated that the interactive media timeline was very feasible to use with the average research data of 4.49, while the feasibility based on the assessment of the media experts stated that the interactive timeline media was very feasible to be used with the research average of the media obtained a score of 4, 26. The research product is effective in improving students' chronological thinking ability with an ngain of 0.68 and is categorized as moderate. Research products are also categorized as very practical by teachers and students with an average value of 4.75 and 4.50.